Answer:
The answer would be 3.33.
Step-by-step explanation:
Simplifying 12x + 5 = 3x + 35
Reorder the terms: 5 + 12x = 3x + 35
Reorder the terms: 5 + 12x = 35 + 3x
Solving 5 + 12x = 35 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation. 5 + 12x + -3x = 35 + 3x + -3x
Combine like terms: 12x + -3x = 9x 5 + 9x = 35 + 3x + -3x
Combine like terms: 3x + -3x = 0 5 + 9x = 35 + 0 5 + 9x = 35
Add '-5' to each side of the equation. 5 + -5 + 9x = 35 + -5
Combine like terms: 5 + -5 = 0 0 + 9x = 35 + -5 9x = 35 + -5
Combine like terms: 35 + -5 = 30 9x = 30
Divide each side by '9'. x = 3.333333333
Simplifying x = 3.333333333
y=2X-5 and 4X-Y=7
Putting the value of Y in 2nd equation:
4x-2x+5=7
2x=7-5
2x=2
OR,x=2/2=1
putting the value of x in equation 1:
y=2x-5
y=2*1-5
y=2-5
y=-3
Answer:
Step-by-step explanation:
Answer:
27
Step-by-step explanation:
if you do pathagorean therom